A Spray-Dried Self-Stabilizing Nanocrystal Emulsion of Traditional Chinese Medicine: Preparation, Characterization and ex vivo Intestinal Absorption - Zhang, Jifen; Xu, Wenxiu; Meng, Fanjing; Yi, Tao (Pharmaceutical Fronts, 2024)
Salvia miltiorrhizae (Danshen, the rhizome of Salvia miltiorrhiza Bge.) and Chuanxiong rhizome (Chuanxiong, the rhizome of Ligusticum chuanxiong Hort.) are two traditional Chinese medicines that have been widely used for the treatment of cardiovascular and cerebrovascular diseases. However, formulation development is difficult due to the complexity of the active ingredients, particularly the water-insoluble tanshinones and volatile oil of Chuanxiong rhizome, which cannot be absorbed via oral administration in conventional dosage forms. This study aimed to develop a self-stabilized nanocrystal emulsion co-loading the water-soluble, insoluble, and volatile active ingredients of Salvia miltiorrhizae and Chuanxiong rhizome to improve the bioavailability of the drugs. In this work, a high-pressure homogenization method was used to prepare a self-stabilizing nanocrystal emulsion. The emulsion was then spray-dried using hydroxypropyl-β-cyclodextrin. The dispersibility and storage stability of the spray-dried emulsion, the particle size and morphology of the emulsion droplets, and the drug content and phase distribution of the reconstituted emulsion were evaluated. An everted intestinal sac model was established, and high-performance liquid chromatography was used to determine the concentration of six active components (ferulic acid, salvianolic acid B, senkyunolide A, ligustilide, cryptotanshinone, and tanshinone IIA) and to assess the cumulative uptake amount of the drug and the apparent permeability coefficient. A mixture of the crude materials of tanshinones extract, total salvianolic acid, ferulic acid, and volatile oil of Ligusticum Chuanxiong was used as a control. The results showed that the spray-dried emulsion can be easily reconstituted into a uniform submicron emulsion with no significant changes in particle size, morphology, and microstructure of the emulsion droplets compared with the original emulsion before drying. The self-stabilizing nanocrystal emulsion significantly improved the intestinal absorption of water-insoluble components (tanshinone IIA, cryptotanshinone, and ferulic acid), and volatile oil components (senkyunolide A and ligustilide). Overall, the spray-dried self-stabilizing nanocrystal emulsion represents a potential oral formulation for Salvia miltiorrhiza and Chuanxiong rhizoma.
Keywords: Salvia miltiorrhizae; Chuanxiong rhizome; nanocrystals; dry emulsion; oral delivery; tanshinones; volatile oil